2019
DOI: 10.24200/amecj.v2.i2.61
|View full text |Cite
|
Sign up to set email alerts
|

Determination of H2S in Crude Oil via a Rapid, Reliable and Sensitive Method

Abstract: Determination of hydrogen sulfide, (H2S) in crude oil is very important due to the environmental impacts, industrial problems and legal international limitation of transportation. In the present work, H2S of crude oil is determined by liquid-liquid extraction followed by potentiometric titration. Three factors including dilution ratio of crude oil with toluene, extraction time of H2S into the caustic phase and API of crude oil was investigated via factorial design. The ANOVA results revealed that the dilution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Also, Shahi Ahangar showed that the photocatalytic removal efficiency in the concentrations of 50, 100, and 300 ppm was equal to 87.8%, 98.9%, and 90.8%, respectively [10]. Many researchers used different pilot and nanoadsorbents (Ni-MWCNTs, GQDs, NGO, NG, MSN, ILs, Silica) to remove hazardous pollutants such as toluene, ethyl benzene, mercury, benzene, dust, and hydrogen sulfide from the air [4,[11][12][13][14][15][16][17][18][19][20]. Finally, according to those mentioned above and the high efficiency of nanoadsorbents compared to other adsorbents in the removal of different materials in the previous studies, a comparison study for adsorption of xylene from the air between commercial activated carbon absorbent and Nano carbon adsorbent was obtained to survey the effect of nanoadsorbent in the removal of xylene from the air.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Shahi Ahangar showed that the photocatalytic removal efficiency in the concentrations of 50, 100, and 300 ppm was equal to 87.8%, 98.9%, and 90.8%, respectively [10]. Many researchers used different pilot and nanoadsorbents (Ni-MWCNTs, GQDs, NGO, NG, MSN, ILs, Silica) to remove hazardous pollutants such as toluene, ethyl benzene, mercury, benzene, dust, and hydrogen sulfide from the air [4,[11][12][13][14][15][16][17][18][19][20]. Finally, according to those mentioned above and the high efficiency of nanoadsorbents compared to other adsorbents in the removal of different materials in the previous studies, a comparison study for adsorption of xylene from the air between commercial activated carbon absorbent and Nano carbon adsorbent was obtained to survey the effect of nanoadsorbent in the removal of xylene from the air.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the exposure to toxic metals (Pb, hg, as, Mn, Al) is dangerous for human health due to the combustion of leaded gasoline. Many metal aerosols and gas pollutants created from crude oil and must be removed from oil before enter to air [6,7]. Moreover, sometimes, the heavy metals generate by recycled products such as battery factories [8,9] and high exposure in air threatens people's health.…”
Section: Introductionmentioning
confidence: 99%